2021
DOI: 10.1007/s00392-021-01965-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative distance and electrocardiographic parameters for lead-implanted site selection to enhance the success likelihood of left bundle branch pacing

Abstract: Background Left bundle branch pacing (LBBP) is a novel near-physiological pacing method that still lacks quantitative criteria to guide the selection of lead-implanted sites to enhance the success likelihood of lead deployments. This study aimed to quantitatively analyze the relationships of LBBP success likelihood to the distribution of lead-implanted sites and the lead-localization-pacing electrocardiographic (ECG) features. Methods All the lead-implanted sites in patients with finally successful LBBP were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…They found that successful pacing sites formed a cluster that was more apical in relation to the tricuspid valve than unsuccessful sites, which were more basal. 12 Interestingly, successful sites also correlated with a leftward paced axis, consistent with a more inferior septal pacing site. It is tempting to speculate that preferential activation of the posterior fascicle is more likely to stimulate the late activated posterior lateral ventricular wall, which is a hallmark in typical LBBB, than anterior fascicle activation.…”
Section: Clinician Questionsmentioning
confidence: 72%
“…They found that successful pacing sites formed a cluster that was more apical in relation to the tricuspid valve than unsuccessful sites, which were more basal. 12 Interestingly, successful sites also correlated with a leftward paced axis, consistent with a more inferior septal pacing site. It is tempting to speculate that preferential activation of the posterior fascicle is more likely to stimulate the late activated posterior lateral ventricular wall, which is a hallmark in typical LBBB, than anterior fascicle activation.…”
Section: Clinician Questionsmentioning
confidence: 72%
“…Lower ∆Paced QRSd meant the paced QRSd was less prolonged, which correlated to a more stable and synchronized ventricular depolarization during follow-up, which might contribute to the maintenance or the improvement of cardiac function. Corrected longit-dist was proposed as a novel distance parameter for describing the position of LBBP lead ( Lu et al, 2021 ). By eliminating the influence of inter-individual variations of cardiac dimension, corrected longit-dist could more accurately reflect the LBBP lead implanted at the upper or lower region of the IVS.…”
Section: Discussionmentioning
confidence: 99%
“…We have invented a coordinate system to describe the distribution of the lead-implanted sites quantitatively ( Lu et al, 2021 ). The definitions of contraction line (CL), distance from CL to apex (CL-apex-dist), longitudinal distance (longit-dist), lateral distance (lat-dist), corrected longit-dist, and corrected lat-dist were described in the Supplementary Materials along with the measuring and conversion methods ( Supplementary Table S1 ) and illustrated in Figure 2B .…”
Section: Methodsmentioning
confidence: 99%
“…The previously described transseptal approach was utilized. 14 , 15 The 3830 lead (1.4 mm, SelectSecure™, Medtronic) was introduced to the RVS via the C315HIS sheath (Medtronic) and screwed to the LBB area. The methodology for lead-implanted site selection was reported in the previous study.…”
Section: Methodsmentioning
confidence: 99%